IMPLEMENTATION OF OCCUPATIONAL SAFETY AND HEALTH AT PT. BUMI GAS INDONESIA ( BGI ) IN THE CIKANDE REGION, BANTEN PROVINCE, INDONESIA - Rieki Indra Bratamanggala; Dewi Puspaningtyas Faeni (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2024)
The level of work accidents and threats to Occupational Safety and Health (OSH/OSH/K3) in Indonesia is still high, especially in the last two years with a significant increase in the number of work accidents. In 2022, there will be 114,235 cases which will increase to 177,161 in 2023, and reach 82,000 cases from January to March 2024. PT Bumi Gas Indonesia (PT BGI), a rapidly growing LPG Gas company, recognizes the importance of implementing Occupational Safety and Health (OSH/OSH/K3 ) in the production process. This research aims to evaluate the implementation of OSH/OSH/K3 at PT BGI. The research method used is qualitative with a descriptive approach, relying on secondary data from relevant literature. The research results show that PT BGI has implemented OSH/OSH/K3 well, including providing personal protective equipment, OSH/OSH/K3 training, and placing fire extinguishers in strategic locations. Effective implementation of OSH/OSH/K3 at PT BGI has been proven to be able to improve work safety, reduce the risk of accidents, and increase company efficiency and productivity. However, several obstacles still exist, such as uneven employee awareness and limitations in implementing OSH/OSH/K3 standards. In conclusion, even though PT BGI has implemented OSH/OSH/K3 well, continued efforts are still needed to optimize the implementation of OSH/OSH/K3, especially through increasing socialization and training for all employees.